Effect of cultivar and grain maturity on NIR spectra of sorghum silages - Santos, VALCICLEIDE OLIVEIRA DOS SANTOS; Bomfim, Marco Aurélio; Santos, Sueli; Tonucci, Rafael; Cavalcante, Ana Clara; Chaves, Ana Karina; Pereira, Patrício Leandro (Pubvet, 2021)
The objective of this study was to evaluate the spectral similarity between sorghum cultivars at different stages of grain maturation, aiming at the development of models using near infrared reflectance spectroscopy (NIRS). For ensiling, sorghums BRS 658 and BRS Ponta Negra were used in PVC mini silos, in the stages of maturation of milky, pasty, farinaceous and hard grains. The variables were studied using the Principal Component Analysis (PCA) technique, and classification using Independent Class Analogy Modeling (SIMCA) using the Unscrambler software. The similarity of silage samples from BRS 658 with the BRS Ponta Negra database was 5% and from BRS Ponta Negra to BRS 658 the similarity was 65%. The data show great similarity of BRS Ponta Negra between the milky and pasty grain stages. The PCA analysis showed a similarity between the samples in the milky stages of the two cultivars, in the milky stage with pasty, farinaceous and hard. The exploratory analysis indicates that it is important to consider the cultivar and the grain maturity stages for the development of NIR sorghum silage models. The analysis of the NIR spectra of the cultivars BRS 658 and BRS Ponta Negra, as well as the stages of maturity at the time of ensiling indicate that the dissimilarities observed add variability to the model, but that, at the same time, they are not so significant as to suggest development of separate models, allowing the merging of data to develop a single
Keywords: Multivariate analysis; spectroscopy; grasses; SIMCA